2014
DOI: 10.5430/jbar.v3n2p36
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators to Clinical Decision Support Systems Adoption: A Systematic Review

Abstract: The objective of the study was to identify potential barriers and facilitators to improve clinical practice using computer-based Clinical Decision Support System (CDSS). Studies published since 2000 were found using PubMed database, PsychInfo, CINAHL, EBSCOhost database, and Google scholar. Twenty-six relevant publications were examined. Thirty-five unique barriers and twenty-five unique facilitators were identified in the literature as important determinants of CDSS's adoption in clinical practice. The list o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 29 publications
2
48
0
Order By: Relevance
“…The instructional topic for the purpose of the case study was decision support systems. This topic included two research papers, which we arranged in the following sequence: 1) "Barriers and Facilitators to Clinical Decision Support Systems Adoption: A Systematic Review" (Devaraj, Sharma, Fausto, Viernes, & Kharrazi, 2014) and 2) "Lessons Learned from Implementing Service-oriented Clinical Decision Support at Four Sites: A Qualitative Study" (Wright et al, 2015). We covered each paper during a two-week online discussion period.…”
Section: Research Design and Participantsmentioning
confidence: 99%
“…The instructional topic for the purpose of the case study was decision support systems. This topic included two research papers, which we arranged in the following sequence: 1) "Barriers and Facilitators to Clinical Decision Support Systems Adoption: A Systematic Review" (Devaraj, Sharma, Fausto, Viernes, & Kharrazi, 2014) and 2) "Lessons Learned from Implementing Service-oriented Clinical Decision Support at Four Sites: A Qualitative Study" (Wright et al, 2015). We covered each paper during a two-week online discussion period.…”
Section: Research Design and Participantsmentioning
confidence: 99%
“…A literature review conducted by Devaraj et al (2014) has identified barriers to performance expectancy of DSS, with the top five being:…”
Section: Lack Of Perceived Usefulnessmentioning
confidence: 99%
“…A study on perceived barriers for a group of rheumatologists discovered a sense of ambivalence relating to concerns that using technology could impair doctor-patient communication (Zong et al, 2015). Many studies have also noted that practitioners are reluctant to use the system in front of patients (Devaraj et al, 2014). This is expected since practitioners do not wish to be perceived as lacking in diagnostic skills or appear to be inefficient in navigating the system.…”
Section: Complex Sociocultural and Economic Factorsmentioning
confidence: 99%
See 2 more Smart Citations